Insights into differentiation and function of the transition region between the seminiferous tubule and rete testis - Figueiredo, A. F.A.; Hess, Rex A.; Batlouni, S. R. [UNESP]; Wnuk, N. T.; Tavares, A. O.; Abarikwu, S. O.; Costa, G. M.J.; França, L. R. (My University, 2021)
Seminiferous tubules physically connect to the rete testis through short segments called the transition region (TR). During fetal development, this specialized junction is considered the initial site where testis cords begin to form and to grow in length well beyond birth and into adulthood and form convoluted tubular cores. Mitotic activity of the Sertoli cell, the somatic cell of the epithelium, ceases before puberty, but modified Sertoli cells in the TR remain immature and capable of proliferation. This review presents what is known about this specialized region of the testis, with an emphasis on the morphological, molecular and physiological features, which support the hypothesis that this short region of epithelial transition serves as a specialized niche for undifferentiated Sertoli cells and spermatogonial stem cells. Also, the region is populated by an elevated number of immune cells, suggesting an important activity in monitoring and responding to any leakage of autoantigens, as sperm enter the rete testis. Several structure/function characteristics of the transition region are discussed and compared across species.
Keywords: Rete testis; Seminiferous tubules; Sertoli cell; Sertoli valve; Transition region; Tubuli recti